Measuring the Efficiency and the Effect of Corporate Governance on the Biotechnology and Medical Equipment Industries in Taiwan - Lee, Yen-Hsien; Huang, Ya-Ling; Hsu, Shiuh-Sheng; Hung, Chien-Han (International Journal of Economics and Financial Issues, 2013)
This study adopts data envelopment analysis with Tobit regression analysis to measure the efficiency and investigate the influence of corporate governance on the efficiency of the biotechnology and medical equipment industries in Taiwan. The empirical results show that while inside equity influences the efficiency of profitability in the pharmaceutical industry, both inside and outside equity influence the efficiency of profitability in the medical equipment industry. Moreover, both inside and outside equity influence the efficiency of marketability in the pharmaceutical and medical equipment industry. The proportion of shares held by foreign institutions is significantly positively correlated with the efficiency of profitability and negatively correlated with the efficiency of marketability, implying that the short-term profit goal of the foreign institutional investors is to sell their holdings. Besides, the number of board members and transparency of information are significantly positively correlated with both the efficiency of profitability and the efficiency of marketability. Keywords: Data Envelopment Analysis; Biotechnology Industry; Corporate Governance; Transparency JEL Classifications: D21; D24; G30; P27